A Dual Interaction Between the 5′- and 3′-Ends of the Melon Necrotic Spot Virus (MNSV) RNA Genome Is Required for Efficient Cap-Independent Translation - Miras, Manuel; Rodríguez-Hernández, Ana M.; Romero-López, Cristina; Berzal-Herranz, Alfredo; Colchero, Jaime; Aranda, Miguel A.; Truniger, Verónica (Frontiers in Plant Science, 2018)
In eukaryotes, the formation of a 5′-cap and 3′-poly(A) dependent protein–protein bridge is required for translation of its mRNAs. In contrast, several plant virus RNA genomes lack both of these mRNA features, but instead have a 3′-CITE (for cap-independent translation enhancer), a RNA element present in their 3′-untranslated region that recruits translation initiation factors and is able to control its cap-independent translation. For several 3′-CITEs, direct RNA-RNA long-distance interactions based on sequence complementarity between the 5′- and 3′-ends are required for efficient translation, as they bring the translation initiation factors bound to the 3′-CITE to the 5′-end. For the carmovirus melon necrotic spot virus (MNSV), a 3′-CITE has been identified, and the presence of its 5′-end in cis has been shown to be required for its activity. Here, we analyze the secondary structure of the 5′-end of the MNSV RNA genome and identify two highly conserved nucleotide sequence stretches that are complementary to the apical loop of its 3′-CITE. In in vivo cap-independent translation assays with mutant constructs, by disrupting and restoring sequence complementarity, we show that the interaction between the 3′-CITE and at least one complementary sequence in the 5′-end is essential for virus RNA translation, although efficient virus translation and multiplication requires both connections. The complementary sequence stretches are invariant in all MNSV isolates, suggesting that the dual 5′–3′ RNA:RNA interactions are required for optimal MNSV cap-independent translation and multiplication.